Perjanjian Perkawinan Sebagai Instrumen Perlindungan Hukum Dalam Perkawinan Poligami Di Indonesia - Aldilla Gemiyu Pawitasari (Universitas Islam Indonesia, 2019)
This research is reviewed from Law No. 1 of 1974 on Marriage (Marriage Law) and Presidential Decree No. 1 of 1991 on Compilation of Islamic Law. Positive Law and Islamic Law only recognize open monogamous marriages, but it does not rule out the possibility for a husband to have a polygamy marriage with the conditions as stated in Article 4 paragraph (2) of the Marriage Law by submitting an application to the Religious Court. The problem formulation is first, how is the application of shared assets in polygamy marriages in Indonesia? Second, how is the legal protection of assets in the polygamy marriage agreement? This research is a normative-juridical study with the aim of finding the coherent truth. The distribution of shared assets in a polygamy marriage is based on an agreement between husband and wife. The first wife is entitled to assets obtained from the marriage between the husband and the second wife, but the second wife is not entitled to the assets of the first husband and wife. To guarantee legal protection for the shared assets, a prenuptial agreement between husband and wives can be concluded so that the problems do not arise in the future. With the prenuptial agreement, positive law and Islamic law protect the rights of the wife, especially regarding the assets obtained during the marriage.